Effect of Remote Vibrotactile Noise on Pinch Force Maintenance Ability and Brain Activity - (:unkn) unknown (My University, 2013)
Noise has been used to enhance detection of signals thereby improving performance of nonlinear systems (referred to as "stochastic resonance"). In biological systems, the noise and signal integration may occur not only at the receptor level but also in the central nervous system, thereby allowing noise remotely applied from a signal to enhance the system's response to the signal. However, integration of tactile signal and noise within the central nervous system has not been demonstrated in humans. In addition, whether the enhanced detection of tactile signals with remote noise results in changes in motor behavior is unknown. The objectives of this thesis were to elucidate the effect of remote vibrotactile noise on hand motor control (Aim 1) and to demonstrate feasibility for quantifying the effect of remote vibrotactile noise on electroencephalography (EEG) activity (Aim 2). Aim 1 found that remote vibrotactile noise had little effect on young, healthy persons' ability to maintain a target pinch force level. While remote noise may have enhanced people's ability to detect very weak signals such as the monofilament stimulation in a previous study, it appears that remote noise was not effective during pinching activity involving strong tactile signals in this thesis. Aim 2 developed methods for quantifying the effect of remote vibrotactile noise on the somatosensory cortex EEG activity in response to monofilament stimulation at the fingertip. A pilot data from one subject showed a trend for strengthened sensation/sensory feedback and sensorimotor information processing, as evidenced by increased peak-to-peak amplitude of event-related potentials and changes in power spectral densities with remote vibrotactile noise at 60% of sensory threshold, but not at 80% and 120% of the sensory threshold. In conclusion, this thesis demonstrated that remote vibrotactile noise did not influence young healthy adults' ability to maintain pinch force. This thesis also demonstrated the ability for quantifying the effect of remote vibrotactile noise on EEG activity in response to fingertip stimulation, with a trend for improved sensory information processing. The results of this thesis may guide future investigation regarding the use of remote vibrotactile noise to influence brain activity, tactile sensing, and motor control.
Keywords: Eeg; Pinch Grip; Remote Vibrotactile Noise; Stochastic Resonance